Ubiquitin Specific Protease 26 (USP26) Expression Analysis in Human Testicular and Extragonadal Tissues Indicates Diverse Action of USP26 in Cell Differentiation and Tumorigenesis - Wosnitzer, Matthew S.; Mielnik, Anna; Dabaja, Ali; Robinson, Brian; Schlegel, Peter N.; Paduch, Darius A. (PLOS ONE, 2014)
Ubiquitin specific protease 26 (USP26), a deubiquitinating enzyme, is highly expressed early during murine spermatogenesis, in round spermatids, and at the blood-testis barrier. USP26 has also been recognized as a regulator of androgen receptor (AR) hormone-induced action involved in spermatogenesis and steroid production in in vitro studies. Prior mutation screening of USP26 demonstrated an association with human male infertility and low testosterone production, but protein localization and expression in the human testis has not been characterized previously. USP26 expression analysis of mRNA and protein was completed using murine and human testis tissue and human tissue arrays. USP26 and AR mRNA levels in human testis were quantitated using multiplex qRT-PCR. Immunofluorescence colocalization studies were performed with formalin-fixed/paraffin-embedded and frozen tissues using primary and secondary antibodies to detect USP26 and AR protein expression. Human microarray dot blots were used to identify protein expression in extra-gonadal tissues. For the first time, expression of USP26 and colocalization of USP26 with androgen receptor in human testis has been confirmed predominantly in Leydig cell nuclei, with less in Leydig cell cytoplasm, spermatogonia, primary spermatocytes, round spermatids, and Sertoli cells. USP26 likely affects regulatory proteins of early spermatogenesis, including androgen receptor with additional activity in round spermatids. This X-linked gene is not testis-specific, with USP26 mRNA and protein expression identified in multiple other human organ tissues (benign and malignant) including androgen-dependent tissues such as breast (myoepithelial cells and secretory luminal cells) and thyroid tissue (follicular cells). USP26/AR expression and interaction in spermatogenesis and androgen-dependent cancer warrants additional study and may prove useful in diagnosis and management of male infertility.